KAJIAN PERUBAHAN SPASIAL GARIS PANTAI SEBAGAI ZONASI TATA RUANG PESISIR (STUDI KASUS PESISIR KABUPATEN KENDAL) - Tjaturahono Budi Sanjoto; Sutrisno Anggoro; Agus Hartoko (Diponegoro University, 2012)
The purposes of this research are to analyze the pattern of coastal spatial changes in Kendal Regency from 1910 to 2009, and to formulate coastal area zoning plan based on spatial changes. The Method of analysed was with overlay technique. Research results show that the coastal spatial changes of produced 5 (five) patterns of coastline changes: (1) coastline spatial change with abrasion pattern, (2) coastline spatial change with accretion pattern, (3) coastline spatial change with accretion pattern folllowed by abrasion, (4) coastline spatial change with accretion pattern then stable, (5) coastline spatial change with stagnant pattern. These spatial changes also altered the shape of Bodri Delta from Cuspate to Lobate. These changes also indicate the alter of geomorphic energy from being destructive to being constructive. Additionally, the research also produced a new product in the form of a map of Kendal District coastal layout zoning.